Development of Effective Risk Mitigation Strategy for Cell Culture Process of Recombinant Protein Production - Yuanita Kumala Dewi; Putu Dana Karningsih (Institut Teknologi Sepuluh Nopember, 2020)
Microbial contamination, instability in production yields and cell lines are the challenges that must be faced by any pharmaceutical biotechnology industry when conducting cell culture as one of the stages of its production process. In the past, Company X has experienced twice contamination cases during cell culture process for its recombinant protein products. As a result, Company X suffered financial lossess at approximately 3.05 billion rupiah and resulted in disruption of the stock of recombinant protein drug which are the active pharmaceutical ingredient for most of injection products. Therefore, an effective mitigation strategies are needed to manage any potential risks in the cell culture process. This study aims to design a risk mitigation strategy for risk in cell culture process by using House of Risk (HOR) method. There are two HOR matrices used in this study. HOR1 is used to determine which risk agents should be prioritized for prevention. In HOR2, several effective risk management strategies will be chosen. There are 40 risks events and 31 risk agents identified. Based on risk assessment results and applying Pareto Chart analysis there are two risk agents selected. Five proactive actions to mitigate these risks are proposed. They are training and personnel qualification program periodically, changing workflow become more efficient and convenient, more detailed revision of related documents, changing manual process to semi-automatic process gradually and additional person on each team as a verifier for double-checking.